The Monkey King 2 [videorecording (DVD)] - Guo, Fucheng, 1965-; Gong, Li, 1965-; Feng, Shaofeng, 1978- (Well Go USA, 2017)
When a traveling monk is stranded in a wasteland, the Monkey King must escort him across the land to retrieve sacred scriptures and protect him from an evil demon.